The Role of Toxicology in Aging Research: An Insight - Rahma, Rahma; Barinda, Agian Jeffilano (Writing Center IMERI FMUI, 2023)
Aging is defined as a time-dependent decline in organ or tissue function. The rate of physiological aging differs among individuals. In addition to genetics, environmental factors contribute to the acceleration of aging. Gerontogen refers to environmental toxicants that can accelerate cellular aging. Toxicology, which is the study of unintended exposures to toxicants, can provide insight into the aging process. Despite the lack of an excellent biomarker to detect aging at the molecular level, several gerontogens, including UV radiation, have been identified. This study will present concise and brief information regarding several biomarkers that can be used to identify gerontogen, as well as a brief explanation of the fundamental mechanism by which gerontogen causes accelerated aging.